Allergic conjunctivitis in a tertiary eye hospital, Nigeria - Fasasi, Monsudi Kehinde; Abdul Kabir, Ayanniyi Ayansiji; Hamza, Balarabe Aliyu; Richard, Azonobi Ifeanyi; Sadiat, Saka Eletu; Abdulfattah, Isa (Journal of Kathmandu Medical College, 2015)
Background: Worldwide, approximately 1/3 of the populations are affected by allergic diseases. Ocular allergy symptoms presented in 40-80% of the affected individuals. Allergic eye disease is a localized allergic condition that is frequently associated with rhinitis and occasionally with asthma. The symptoms and signs can manifest as conjunctivitis, blepharitis, blepharoconjunctivitis, or keratoconjunctivitis. Objective: To determine the pattern of presentation of ocular allergy in the study population and to create awareness among health professional and the public. Methods: A four months hospital based cross sectional study involving administration of self explained structured questionnaires to all consented patients that presented at our eye care facility on accounts of ocular itching during the study period was conducted. All the patients had comprehensive eye assessment by consultant ophthalmologist. Data was analyzed with SPSS version 18 Results: Of 200 patients that presented with conjunctivitis during the study period 163 (82%) patients were due to allergic conjunctivitis. There were 80 males and 83 females. Majority (43.6%) of the patients were within the age groups of 17 years-33 years, followed by 0-16 years (42.3%). Majority of the patients 102 (62.3%) presented with symptoms of ocular itching and redness. Only 18 (11%) of the patients were a known asthmatic. However, 73 (44.8%), 87 (53.4%) and 79 (48.5%) of these patients have family history of asthma, atopy and ocular allergy respectively. Most of the patients 161 (98.8%) were treated with medication, while only two patients had surgical intervention (cornea ulcer debridement). Conclusion: Allergic conjunctivitis is the commonest reasons why patients present with conjunctivitis at our eye clinic and it is commonest in the active age group. Eye health education about ocular allergy is underscored. Journal of Kathmandu Medical College Vol. 3, No. 4, 2014 Page: 149-152